Graphical evaluation of the geometric tooth form: A gender-based AutoCAD analysis of maxillary central incisor - Sneha Mantri; Kailash Asawa; Nagesh Bhat; Surekha Godbole; Shivkumar Mantri; Akashdeep Singh Bal (Wolters Kluwer Medknow Publications, 2022)
Background: No universally accepted parameter exists for selecting/restoring the form of maxillary central incisors (MCIs). Aim: The purpose of this cross-sectional, observational clinical study was to digitally determine the prevalent form of MCIs among males and females of the Central Indian population with AutoCAD software. Materials and Methods: This is a clinical study comprising 200 dental and engineering students (female: 100; male: 100) aged between 18 and 35 years. The pictures of the right (MCI) of each participant were clicked. The images were calibrated in the vertical position to standardize according to the long axis of the tooth. The AutoCAD computer program was used to evaluate the geometric form of the tooth graphically. The results revealed that the tooth form was classified as oval, triangular, or quadrangular. The intergroup comparison using one-way analysis of variance was made, followed by the intragroup comparison using Tukey's test for quantitative data. For comparison between males and females based on tooth form, the data were assessed using Student's t-test as quantitative analysis, and for qualitative assessment, Chi-square test was used. The significance level was set at 0.05. Remeasuring 40 samples from each group tested intraexaminer consistency by applying Bland-Altman and scatter regression analysis. Results: Males had 57% oval, 29% tapered, and 14% quadrangular, while females had 60% oval, 23% tapered, and 14% quadrangular tooth form. Conclusions: The oval tooth form was the most common, both in males and females, followed by the tapered and the quadrangular form. No gender variation was seen in tooth forms.